Level of Knowledge and Incidence of Emergency Oncology: Febrile Neutropenia in Hematologic Cancer Patients Post Chemotherapy: A Descriptive Study - Agus Suryaman (IKesT Muhammadiyah Palembang, 2024)
Introduction: Febrile neutropenia is a life-threatening condition that is the most common oncological emergency, especially in cases of hematological cancer. Knowledge related to this condition can accelerate treatment and reduce mortality. The danger of this condition is not accompanied by sufficient information about it, research related to this is very rare, especially in Indonesia, including the incidence and knowledge of patients about febrile neutropenia. Objective: This study aims to determine the level of knowledge and incidence of febrile neutropenia in hematological cancer patients after chemotherapy. Method: This study used a quantitative descriptive design with a cross-sectional approach. The sampling technique used purposive sampling in hematologic cancer patients after chemotherapy at Dr. Mohammad Hoesin Hospital, Palembang, with a sample size of 40 respondents. Results: The results of the study showed that 26 respondents (65%) experienced neutropenia, and of that number, 8 respondents (35%) developed febrile neutropenia. Level of knowledge related to febrile neutropenia, as many as 25 respondents (62.5%) have low knowledge about febrile neutropenia. Discussion: febrile neutropenia post chemotherapy is riskier when the patient is at home, knowledge related to this problem is very important to prevent more dangerous conditions or death.